Comparison of the efficacy of endoscopic submucosal dissection and transanal endoscopic microsurgery in the treatment of rectal neuroendocrine tumors ≤ 2 cm - Jin, Rui; Bai, Xiaoyin; Xu, Tianming; Wu, Xi; Wang, Qipu; Li, Jingnan (Frontiers in Endocrinology, 2023)
Introduction Currently, complete tumor resection is considered the most effective treatment for rectal neuroendocrine tumors (NETs). Endoscopic submucosal dissection (ESD) and transanal endoscopic microsurgery (TEM) are recommended for rectalNETs ≤2 cm, but it is not clear which method is better. Thus, we evaluated the efficacy of ESD and TEM in the treatment of rectal neuroendocrine tumors (NETs) ≤ 2 cm. Methods We conducted a single-centre retrospective cohort study between 2010 and 2021 of rectal NETs ≤ 2 cm in 114 patients with long-term follow-up data who were divided into ESD (n=55) and TEM groups (n=59). Our study assessed differences between groups in the complete resection rate of lesions, recurrence rate, surgical complications, procedure time, and length of hospital stay. Results The co-primary outcomes were the complete resection rate of lesions and the recurrence rate. Compared to that in the ESD group, the complete resection rate was significantly higher in the TEM group (91.5% vs. 70.9%, p=0.005). The median follow-up time was 22 months in our study, and the follow-up outcomes suggested that the rates of recurrence were 1.8% (1/55) and 6.8% (4/59) in the ESD and TEM groups, respectively, with no significant difference between the two groups. The secondary outcomes of the evaluation were surgical complications, procedural time, and length of hospital stay. The rate of complications (gastrointestinal bleeding and perforation) was low in both the ESD (7.3%, 4/55) and TEM (5.1%, 3/59) groups. No difference in hospitalization duration was observed between the two groups in our study. However, the procedure time was significantly shorter in the ESD group than in the TEM group (27.5 min vs. 56 min, p<0.001). Conclusions Although the rate of complete resection in the TEM group was higher than that in the ESD group, there was no difference in recurrence rates between the two modalities during long-term follow-up. Depending on the qualities of the available hospital resources in the area, one of the two approaches can be adopted.